The metabolomics of oxidative stress. (April 2015) - Noctor, Graham; Lelarge-Trouverie, Caroline; Mhamdi, Amna
Graphical abstract: We discuss how the metabolite profiles of plants are influenced by increased production of reactive oxygen species and associated changes in cellular redox state. Highlights: Oxidative stress can impact plant metabolite profiles in multiple ways. Accurate measurement of specific reactive oxygen species is not simple. Both primary and secondary metabolism pathways respond to oxidative stress. Potential metabolite markers of oxidative stress are discussed. Relationships between oxidative stress and phytohormone signalling are emphasized. Abstract: Oxidative stress resulting from increased availability of reactive oxygen species (ROS) is a key component of many responses of plants to challenging environmental conditions. The consequences for plant metabolism are complex and manifold. We review data on small compounds involved in oxidative stress, including ROS themselves and antioxidants and redox buffers in the membrane and soluble phases, and we discuss the wider consequences for plant primary and secondary metabolism. While metabolomics has been exploited in many studies on stress, there have been relatively few non-targeted studies focused on how metabolite signatures respond specifically to oxidative stress. As part of the discussion, we present results and reanalyze published datasets on metabolite profiles in catalase-deficient plants, which can be considered to be model oxidative stress systems. We emphasize the roles of ROS-triggered changes in metabolites as potential oxidative signals, and discuss responses that might be useful as markers for oxidative stress. Particular attention is paid to lipid-derived compounds, the status of antioxidants and antioxidant breakdown products, altered metabolism of amino acids, and the roles of phytohormone pathways.